The Influence of Merdeka Curriculum and Learning Motivation on Student’s Learning Outcomes - Hikdawati, Herisa Aji; Arafat, Yasir; Putra, Muhammad Juliansyah (Graduate Program Magister Manajemen Pendidikan, 2024)
This research aims to determine and analyze: (1) The influence of the Merdeka curriculum on Student Learning Outcomes; (2) The influence of learning motivation on student learning outcomes; (3) The influence of the Merdeka curriculum and Learning Motivation together on student learning outcomes. This research was conducted at SMAN 1 Payaraman with a sample of 117 students. Data collection techniques use questionnaires and documentation. Test the validity of the data using the bivariate correlations test, and test the reliability using the Cronbach Alpha test. Test prerequisites for analysis using normality test, linearity test, and multicollinearity test. For data analysis use correlation test data analysis and linear regression test. The research results show that; (1) there is no significant influence between the Merdeka curriculum on student learning outcomes, (2) there is a significant influence between learning motivation on student learning outcomes at SMAN 1 Payaraman, (3) there is a joint influence between the Merdeka curriculum and learning motivation on student learning outcomes at SMAN 1 Payaraman with an influence of 6.7%. The remaining 93.3% is influenced by factors that are not variables in this research.